PENGEMBANGAN BAHAN AJAR BERBASIS E-BOOK PADA MATA PELAJARAN IPA MATERI PENGGOLONGAN HEWAN BERDASARKAN JENIS MAKANANNYA DI SD NEGERI SERANG 20 - Novia Monitha; Encep Andriana; Trian Pamungkas Alamsyah; Nana Hendracipta (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article covers the explanation of the teaching materials feasibility in the form of digital books or e-books to support students‟ learning, especially in Natural Sciences subject matter and the student‟s responses to teaching materials developed by the researchers. The research method used described in this article was Research and Development (R&D) by using the Borg and Gall developmental model that consisted of potential and problems, data collection, product design, design validation, design revision, and a limited product trial. The results showed the feasibility of e-books was seen based on the assessment of design experts, linguists and material experts. The scores obtained were 81.305% from the design experts, 81.53% from the Linguists, and 91.42% from material experts. Subsequently, for student responses to e-books used in the learning process, the average score was 0.958 or 96%. Based on the results, it could be concluded that the research produced an e-book of the natural sciences materials on the animal classification based on their type of foods at class V students in Elementary School. The results of design validation indicated the „Very Eligible‟ category, Linguist validation indicated the „Very Eligible‟ category, and material validation indicated the „Very Eligible‟ category. The students‟ responses category encompassed the „Very Good‟ category. Thus, the product resulted was categorized to be suitable for use as teaching materials in the online learning process.